The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12864-019-6236-6
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic profile of topping responsive non-coding RNAs in tobacco roots (Nicotiana tabacum)

Abstract: BackgroundNon-coding RNAs (ncRNAs), including microRNAs (miRNAs), long ncRNAs (lncRNAs) and circular RNAs (circRNAs), accomplish remarkable variety of biological functions. However, the composition of ncRNAs and their interactions with coding RNAs in modulating and controlling of cellular process in plants is largely unknown. Using a diverse group of high-throughput sequencing strategies, the mRNA, miRNA, lncRNA and circRNA compositions of tobacco (Nicotiana tabacum) roots determined and their alteration and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…In recent years, the availability of diverse germplasms and high-throughput sequencing platform provided an opportunity to study secondary metabolism. Although many genes involved in nicotine biosynthesis and regulation have been reported, the studies about small RNA’s role are elusive 56 . In our work, three important high-throughput methods, namely, small RNA, degradome and transcriptomics sequencing were applied to investigate mechanisms of nicotine biosynthesis in tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the availability of diverse germplasms and high-throughput sequencing platform provided an opportunity to study secondary metabolism. Although many genes involved in nicotine biosynthesis and regulation have been reported, the studies about small RNA’s role are elusive 56 . In our work, three important high-throughput methods, namely, small RNA, degradome and transcriptomics sequencing were applied to investigate mechanisms of nicotine biosynthesis in tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a total of 1593 lncRNA loci (2206 isoforms) were identified in C. hytivus based on stringent criteria. lncRNAs were also identified in other polyploid plants, example given bread wheat (44,698) [ 77 ], cotton (8514) [ 34 ], tobacco (7423) [ 78 ], and Brassica napus (549) [ 79 ]. The identification efficiency of lncRNAs may be affected by their reference genome, RNA sequencing methods, and different identification strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Raw sequence data of different tissues were obtained from PLncDB ( http://plncdb.tobaccodb.org/ ) ( Jin et al, 2021 ) and our unpublished data. Raw RNA-seq datasets, including cold ( Jin et al, 2017 ), drought ( Yang H et al, 2017 ), cadmium (Cd) ( He et al, 2016 ), topping ( Chen et al, 2019 ), NaCl, abscisic acid (ABA) ( Wu et al, 2021 ), cucumber mosaic virus (CMV) ( Liu et al, 2019 ), and Phytophthora nicotianae ( Yang J. K et al, 2017 ) were obtained from the SRA database ( Leinonen et al, 2010 ). All clean reads were mapped to the tobacco reference genome using Hisat2 (2.2.1) ( Kim et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%